Race components influence in 100 - meter backstroke - Izov, N. (2nd International scientific conference "Sport, recreation, health", 12th & 13th May, 2017, Belgrade, 2017)
Regular competition analyses of world swimming elite provide useful information about the tendencies in training. The aim of our research is to reveal the influence of race components in men`s 100-meter backstroke. We used official data about Rome 2009 finalists. The changes of swimvelocity, stroke rate and stroke length were analyzed, as well as the relation between race components and 100-meter backstroke result. We used descriptive statistics and correlation for statistical analysis. The findings show that swimmers decrease their speed throughout the race by decreasing stroke frequency and stroke length in different extent. The values of these parameters increase for some parts of the race but there is no consistent pattern regarding their changes. Good start and turn with fast underwater swimming are of great importance for the 100-meter backstroke result. Proper pacing during the first 25 meters right after breaking the surface contributes for saving energy, better second half and better result.